Trends in E-Business, E-Services, and E-Commerce: Impact of Technology on Goods, Services, and Business Transactions - In Lee (USA Business Science Reference, 2013)
The emergence of internet technologies have provided organizations and customers with access to vast amounts of data, information, and services which have revolutionized the process of exchanging products and services online. Trends in E-Business, E-Services, and E-Commerce: Impact of Technology on Goods, Services, and Business Transactions provides insights into issues, challenges, and solutions related to the successful application and management aspects of electronic business. This book will bring together a comprehensive framework for researchers and practitioners in understanding the growing demand of e-business research.
Keywords: E-business; E-commerce; E-services; Business; Textbooks; (BIN3025-N) Emerging Technologies for the Enterprise